2017
DOI: 10.1108/tqm-06-2017-0068
|View full text |Cite
|
Sign up to set email alerts
|

The role of technology and institutions in tourism service ecosystems

Abstract: Purpose Given the growing attention on service ecosystem and the role played by technology and institutions in shaping of actors’ relations and interactions, the purpose of this paper is to examine a tourism environment with the lens of service ecosystem in order to derive a deeper understanding on the underlying mechanisms. Design/methodology/approach A mixed methodology was used. First, literature review based on service ecosystems framework was conducted to critically analyze the roles of technology and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 84 publications
3
69
0
Order By: Relevance
“…Despite the exploration of the role of actors' engagement and resource integration in fostering innovation in some contributions from S-D logic [8], the drivers for service innovation have been not been systematized in service research. Furthermore, the nature of the relationship between technologies and value co-creation has not yet been clarified [26].…”
Section: Technology Value Co-creation and Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the exploration of the role of actors' engagement and resource integration in fostering innovation in some contributions from S-D logic [8], the drivers for service innovation have been not been systematized in service research. Furthermore, the nature of the relationship between technologies and value co-creation has not yet been clarified [26].…”
Section: Technology Value Co-creation and Innovationmentioning
confidence: 99%
“…Moreover, the significance of interactive features leads to the introduction of other key enabling dimensions, such as users' engagement and empowerment, that can modify the value co-creation experience [54] which is built collaboratively during the interaction between actors. Then, according to a social vision, context-based variables (such as institutions in work based on a service ecosystems view [26]) and an actor's attitude [55,56], capabilities, and their specific performing roles are viewed as external variables that can shape the value co-creation process.…”
Section: Technology Value Co-creation and Innovationmentioning
confidence: 99%
“…Our findings are consistent with results of [41] found that, cloud computing offers solutions spread across the wide-spectrum of information technologies and hence will consolidate its position as a viable model in the years to come, also Similarly, [42] stated that cloud computing offers multiple advantages to (SME) that these advantages motivate several enterprises to consider outsourcing their applications (business processes) to this emerging computing environment. As [43] findings reveal that usage of technology in the field of tourism, can adjusting the tourism service ecosystem.…”
Section: Resultsmentioning
confidence: 91%
“…First, it is confirmed that technology and other institutional arrangements, such as norms, practices and symbols, cannot work in isolation but should consider the existing structures of the service ecosystems into which they are introduced (Barile et al, 2017). In other words, the technological focus of SSs must be complemented by the institutional focus of S-D l. Indeed, in the presented example, introducing mechanisms of collective intelligence (by means of collective knowledge systems) for rumor detection or even introducing automatic systems for fake news detection without leveraging users' engagement is a useless job because communities need to know and feel OSNs' attempts to align with their needs and take care of them to foster users' participation and to reduce misinformation.…”
Section: Implications and Conclusionmentioning
confidence: 99%